Lactobacillus brevis Alleviates DSS-Induced Colitis by Reprograming Intestinal Microbiota and Influencing Serum Metabolome in Murine Model - Ding, Sujuan; Ma, Yong; Liu, Gang; Yan, Wenxin; Jiang, Hongmei; Fang, Jun (Frontiers in Physiology, 2019)
The aim of this study was to examine the effects of Lactobacillus brevis on the microbial community and serum metabolome in colitis induced by dextran sulfate sodium (DSS). ICR mice were randomly distributed into three treatment groups: (i) Lactobacillus brevis treatment alone (control), (ii) DSS administration alone, and (iii) treatment with Lactobacillus brevis and DSS. Our results demonstrate that Lactobacillus brevis treatment significantly alleviated DSS-induced body weight loss and colon inflammation. In addition, LC-MS analysis of serum metabolites revealed that Lactobacillus brevis treatment increased the serum level of metabolites against inflammatory responses or oxidative stressors caused by DSS in the murine model. By detecting colonic microbiota, Lactobacillus brevis increased colonic microbial diversity after challenging with DSS, and increased the relative abundance of Alloprevotella at genus, but Bacteroidales was reduced (P < 0.05). These result indicated that Lactobacillus brevis could lower the severity of colitis induced by DSS via improving reprogramming the serum metabolome and intestinal microbiota. These findings suggest that the probiotic Lactobacillus brevis may prevent tissue damage from colitis.